Application of solar-induced ventilation prototype in Small and Medium Enterprise building - Mohammad Yusoff, Wardah Fatimah; Sapian, Abdul Razak; Salleh, Elias; Adam, Nor Mariah; Johar , Suhana (International Society of the Built Environment, 2015)
This paper discusses the application of a solar-induced ventilation strategy in a small and medium enterprise (SME) building, which is a single-storey shophouse. The aim of the study was to examine the performance of the proposed strategy to enhance the indoor environment of the selected building. The proposed strategy comprises two parts, namely roof solar collector and vertical stack. The research method employed a simulation modelling, which was validated against field measurement. The findings indicated that the proposed strategy was able to reduce the indoor air temperature, as well as increase the indoor air flow rate and air exchange rate of the SME building. The highest indoor air temperature reduction was 1.8C, while the highest indoor air flow rate and air exchange rate enhancement were 0.08 m3/s and 16 ACH, respectively. In summary, the findings highlighted the potential application of the proposed strategy in enhancing the indoor environment of a SME building. The combination of roof solar collector and vertical stack was demonstrated to enable enhancement of the stack ventilation, to provide high ventilation rates especially for buildings with deep plan layout, by increasing the temperature difference between the inside and outside air, as well as the vertical difference between the inlet and outlet.